From Stress Reduction to Resilience Building: The Role of Yoga in Promoting Mental Health and Well-Being - Veckalne, Regina (Researchparks Publishing, 2023)
In recent years, there has been a growing interest in the use of yoga as an intervention for promoting mental health and well-being. This article explores the role of yoga in stress reduction and resilience building, with a focus on its potential benefits for individuals experiencing mental health difficulties. A review of the literature suggests that regular practice of yoga can lead to significant reductions in stress, anxiety, and depression, as well as improvements in mood, self-esteem, and quality of life. Moreover, yoga has been shown to enhance the body's stress response systems, promoting greater resilience to stress and adversity. The neurobiological mechanisms underlying these effects are also discussed, highlighting the potential role of yoga in modulating key brain regions and neurochemical pathways involved in stress regulation and emotional processing. Overall, the evidence suggests that yoga is a promising intervention for promoting mental health and well-being, with potential benefits for individuals across the lifespan. Future research is needed to better understand the mechanisms underlying these effects and to optimize the use of yoga as a tool for enhancing mental health and resilience.